Structure and thermal behavior of PMMA-polysilsesquioxane organic-inorganic hybrids - Pereira Carvalho, Hudson Wallace [UNESP]; Suzana, Ana Flavia [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier B.V., 2014)
PMMA-polysilsesquioxane (PMMA-Sil) class II organic-inorganic hybrids were prepared by the sol-gel method from a PMMA-based polymer precursor containing trimethoxysilane groups. An analysis was made of the effect of siloxane content, adjusted by addition of tetraethyl orthosilicate (TEOS), on the structure and thermal stability of the dried gels. C-13 nuclear magnetic resonance measurements confirmed PMMA as the organic phase, while Si-29 measurements revealed the presence of both T and Q silicon species, the most abundant being T-2 and Q(3). X-ray diffraction results showed that the inorganic SiO2 phase was amorphous, while small angle X-ray scattering analyses indicated that the average gyration radius size of the silicate particles and the correlation distance between the particles increased with greater addition of TEOS. Thermal stability was improved by increasing the amount of the inorganic phase. This effect was more evident under an air atmosphere than under N-2, indicating that the silicate phase acted to limit oxygen diffusion. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Hybrid nanocomposites; NMR; SAXS; Thermal stability; PMMA; TEOS